Maternal parenting behavior and functional connectivity development in children: A longitudinal fMRI study. (April 2021) - Pozzi, Elena; Vijayakumar, Nandita; Byrne, Michelle L.; Bray, Katherine O.; Seal, Marc; Richmond, Sally; Zalesky, Andrew; Whittle, Sarah L.
Highlights: Longitudinal study with two waves of imaging data and observational measures of parenting. We examined functional connectivity of amygdala and selected large-scale networks. We detected developmental effects as a function of parenting. Positive parenting was associated with decreased control network connectivity. Positive parenting behavior may promote resting state network maturation. Abstract: Parenting behavior is associated with internalizing symptoms in children, and cross-sectional research suggests that this association may be mediated by the influence of parenting on the development of frontoamygdala circuitry. However, longitudinal studies are lacking. Moreover, there is a paucity of studies that have investigated parenting and large-scale networks implicated in affective functioning. In this longitudinal study, data from 95 (52 female) children and their mothers were included. Children underwent magnetic resonance imaging that included a 6 min resting state sequence at wave 1 (mean age = 8.4 years) and wave 2 (mean age = 9.9 years). At wave 1, observational measures of positive and negative maternal behavior were collected during mother-child interactions. Region-of-interest analysis of the amygdala, and independent component and dual-regression analyses of the Default Mode Network (DMN), Executive Control Network (ECN) and the Salience Network (SN) were carried out. We identified developmental effects as a function of parenting: positive parenting was associated with decreased coactivation of the superior parietal lobule with the ECN at wave 2 compared to wave 1. Thus our findings provide preliminary longitudinal evidence that positive maternal behavior is associated with maturation of the connectivity between higher-order control networks.